Clinical and histomorphometric comparison of autologous dentin graft versus a deproteinized bovine bone graft for Socket Preservation - Gallusi Gianni; Quinzi Vincenzo; Grilli Filippo; Memè Lucia; P. Rasicci; Mummolo Stefano (Publymed, 2020)
Dentin has been an important topic of study for its potential use as a bone substitute because it has a higher mineral content than any material derived from bone. Furthermore, dentin is similar to autologous bone in two ways: it is both osteocompatible and osteoconductive, thus providing a physical matrix for the sediment of new bone.